2021
DOI: 10.1108/ecam-01-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Identifying focus areas to decode the decision to litigate contractual disputes in construction

Abstract: PurposeStrong and independent judiciary symbolizes transparency and impartiality in the dispute resolution process. However, litigation is often time-consuming and affects the working relationship between the disputants. In the construction context, where projects typically have a short life span of three to four years, dispute resolution through litigation induces unaffordable process delays. Despite the inherent challenges associated with litigation, it is observed that disputing parties resort to litigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…The individual and project-level “focus areas” (frame-influencers) influencing the TTL have been identified by Marzouk et al. (2011) and Jagannathan and Delhi (2022). Therefore, there is a need to develop a larger unified model to understand the TTL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual and project-level “focus areas” (frame-influencers) influencing the TTL have been identified by Marzouk et al. (2011) and Jagannathan and Delhi (2022). Therefore, there is a need to develop a larger unified model to understand the TTL.…”
Section: Discussionmentioning
confidence: 99%
“…However, when an amicable settlement fails, the tendency to litigate (TTL) surfaces (Jagannathan and Delhi, 2020). Once the litigation worthiness of the dispute is evaluated at the individual and project levels (Jagannathan and Delhi, 2022), the decision to litigate rests with the organisation. While the litigation tendencies take shape, progressing from an individual level to a project level and finally reaching the organisation level, in this study, the scope is limited to identifying an organisation's financial conditions influencing litigation motives.…”
Section: Introductionmentioning
confidence: 99%
“…Per the FTL framework, a dispute with risks but higher returns (compared to the settlement offer) increases the claimant's tendency to litigate. The extent of risk and return, in turn, depends on the contractual and legal merit of the dispute (Jagannathan and Delhi, 2022). Thus, the decision to proceed further on the litigation path is influenced by the complexity of the dispute, and the same requires empirical testing (Rachlinski, 1996).…”
Section: Literature Review To Identify the Frame Influencersmentioning
confidence: 99%
“…In the construction context, researchers identify factors leading to litigation of contractual disputes (Almutairi et al, 2015;Jagannathan and Delhi, 2022;Marzouk et al, 2011). In general, it is observed that litigation is imminent if attempts to resolve disputes through alternate dispute resolution (ADR) mechanisms fail (Sambasivan and Soon, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A construction organization is different and often marred by uncertainties and risks of a higher degree when compared to other organizations (Das, 2018). The uniqueness of the construction sector (Jagannathan and Delhi, 2022) demands a more detailed factor-wise view of various aspects that may impact the functioning of a construction organization. In fact, researchers recommend considering a special focus (Chan, 2020) on the construction sector, given its diverse yet interconnected features.…”
Section: Introductionmentioning
confidence: 99%